Binding of ribosomes to 5'-terminal leader sequences of eukaryotic messenger RNAs. - Filipowicz, W (1979)
Tobacco mosaic virus and turnip yellow mosaic virus genome RNAs, which have long (greater than or equal to 69 nucleotides) 5'-terminal leader sequences preceding the AUG initiation codon, can form disome initiation complexes when incubated with a wheat germ extract and sparsomycin. In tobacco mosaic virus RNA, whereas one ribosome in such complexes presumably occupies the AUG-containing initiation site, the other is located within the RNA leader sequence. The results favor a model of eukaryotic initiation in which ribosomes first bind to the 5' end of the mRNA independently of AUG, then advance to the AUG initiation codon, where protein synthesis ensues.